DIAMACC: protocol of a prospective diagnostic accuracy study of the maximal systolic acceleration to detect peripheral arterial disease in patients with diabetes-related foot ulceration in the Netherlands - Jaap Hamming; Siem Willems; Abbey Schepers; Jeroen J W M Brouwers (BMJ Open)
Introduction Foot ulcers are one of the most serious complications of diabetes, leading to significant risks on amputation and mortality. Peripheral arterial disease (PAD) is an important factor for the development and the outcome of diabetic foot ulcers (DFU). Although prompt and accurate detection of PAD is critical to reduce complications, its diagnosis can be challenging with currently used bedside tests (such as ankle–brachial index and toe pressure) due to medial arterial calcification. A new and promising bedside test for the detection of PAD is the maximal systolic acceleration (ACCmax), measured by duplex ultrasonography (DUS). The primary aim of this study is to assess the diagnostic performance of the ACCmax to detect PAD in patients with DFU, in comparison with commonly used bedside tests. Secondary aims include the correlation between diagnostic test accuracy and patient comorbidities. Tertiary objectives focus on collecting (follow-up) data for prognostic evaluation, such as ulcer healing, revascularisation feasibility, amputation risk, cardiovascular events and mortality.Methods and analysis A multicentre prospective diagnostic accuracy study with 198 patients will be conducted to assess the diagnostic performance of multiple index tests to detect PAD in patients with DFU, with special emphasis on ACCmax. A full lower limb arterial DUS will serve as reference test.Ethics and dissemination Study protocol approval was gained from the Medical Ethical Committee Leiden/Den Haag/Delft and registered at ClinicalTrials.gov. The findings of this study will be reported through peer-reviewed publications and (inter)national conferences.Trial registration number NCT05646147.